2012
DOI: 10.1161/circep.111.964635
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Study of Ventricular Scar in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(57 citation statements)
references
References 56 publications
4
46
2
1
Order By: Relevance
“…In a study of 30 subjects who were suspected of having ARVD/C, RV LGE was found in 67% of those who were eventually given a diagnosis of ARVD/C and in none of 18 subjects without the diagnosis (6). Marra et al (22) found RV LGE in 39% of 23 subjects with ARVD/C. In contrast, we found RV LGE in only 16% of our 76 subjects with ARVD/C, and it localized mostly to the inferior wall.…”
Section: Cardiac Imaging: Fibrofatty Changes At Cardiac Mr Imaging Incontrasting
confidence: 87%
“…In a study of 30 subjects who were suspected of having ARVD/C, RV LGE was found in 67% of those who were eventually given a diagnosis of ARVD/C and in none of 18 subjects without the diagnosis (6). Marra et al (22) found RV LGE in 39% of 23 subjects with ARVD/C. In contrast, we found RV LGE in only 16% of our 76 subjects with ARVD/C, and it localized mostly to the inferior wall.…”
Section: Cardiac Imaging: Fibrofatty Changes At Cardiac Mr Imaging Incontrasting
confidence: 87%
“…A study on the comparison between deformation imaging derived regional abnormalities and electrical abnormalities found during an electrophysiological study has to be performed to validate the current findings in electromechanical dyssynchrony. Validation is of particular importance since a recent study showed a weak correlation between late gadolinium contrast enhanced regions by MRI and the electro-anatomical scar a by electrophysiological study [60].…”
Section: Discussionmentioning
confidence: 99%
“…23 Contrast-enhancement-cardiac magnetic resonance is less sensitive to identify right ventricular scar lesion but is the only tool able to detect early subepicardial LV involvement that can be the first manifestation of the disease in otherwise functionally normal hearts. 24 3.1.3 How is the cost effectiveness of alternative diagnostic methods to be judged? When a pathogenic mutation has been found in the index patient, genetic screening can be offered to first-degree relatives (cascade genetic screening) to determine whether they carry the same mutation and may be at risk of developing the disease in the future.…”
Section: Describe the Burden Of Alternative Diagnostic Methods To Thementioning
confidence: 99%